2017
DOI: 10.1016/j.euroecorev.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Normative conflict and the limits of self-governance in heterogeneous populations

Abstract: Mechanisms to overcome social dilemmas provide incentives to maximize efficiency. However, oftensuch as when agents are heterogeneousthere is a trade-off between efficiency and equalitya normative conflictwhich is overlooked. Agents' concerns for equality in such instances can limit the ability of mechanisms to promote efficiency. We provide evidence for this from a public good experiment using a simple mechanism allowing individuals to communicate periodically with other group members and reward them for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 67 publications
2
35
0
Order By: Relevance
“…A large body of experimental research in economics and other social sciences explores the role of communication in various types of economic interactions, such as cooperation, coordination, trust and reciprocity (see, among others, Ostrom et al, 1992;Cooper et al, 1992;Charness, 2000;Duy and Feltovich, 2002;Ellingsen and Johannesson, 2004;Duy and Feltovich, 2006;Bochet and Putterman, 2009;Bracht and Feltovich, 2009;Gangadharan et al, 2017). This body of empirical evidence generally points to the conclusion that communication increases the eciency of interactions (Sally, 1995;Crawford, 1998;Balliet, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of experimental research in economics and other social sciences explores the role of communication in various types of economic interactions, such as cooperation, coordination, trust and reciprocity (see, among others, Ostrom et al, 1992;Cooper et al, 1992;Charness, 2000;Duy and Feltovich, 2002;Ellingsen and Johannesson, 2004;Duy and Feltovich, 2006;Bochet and Putterman, 2009;Bracht and Feltovich, 2009;Gangadharan et al, 2017). This body of empirical evidence generally points to the conclusion that communication increases the eciency of interactions (Sally, 1995;Crawford, 1998;Balliet, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…additional mechanisms are equally effective. For example, Gangadharan et al (2017) find that communication increases cooperation in both homogeneous and heterogeneous groups, but the positive effect of communication is stronger in homogeneous groups. Finally, not all studies find that heterogeneity is detrimental to efficiency, and not under all circumstances.…”
Section: Introductionmentioning
confidence: 95%
“…A large body of previous work has found that heterogeneity in endowments, productivity and/or returns frequently reduces cooperation in VCM games (e.g. Cherry et al 2005, Anderson et al 2008, Tan 2008, Nikiforakis et al 2012, Fischbacher et al 2014, Hargreaves Heap et al 2016, Gangadharan et al 2017). 2 This is primarily due to a multiplicity of norms that underlie the behavior of players with different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…But mechanisms that work when populations face the same opportunities and derive the same benefits from the collective goods may not be as effective when populations are heterogeneous in that respect. Indeed, the tension between private and social interests can be aggravated in such groups because of increased inequality and the presence of normative conflicts regarding what one ought to do in such circumstances (Gangadharan, Nikiforakis, & Villeval, ; Nikiforakis, Noussair, & Wilkening, ; Reuben & Riedl, ; Weng & Carlsson, ). This raises the question of which policy intervention can be effective in such environments, both with regard to reduced free‐riding and more equal income distribution.…”
Section: Introductionmentioning
confidence: 99%